Far from easy and accurate - detection of metabolic syndrome by general practitioners - Mäntyselkä Pekka; Helminen Eeva-Eerika; Nykänen Irma; Kumpusalo Esko (BMC Family Practice, 2009)
Abstract Background Metabolic syndrome (MetS) is a major public health challenge. General practitioners (GPs) could play a key role in its recognition. However, it often remains undiagnosed in primary care. This study assesses how well GPs and patients recognise MetS among patients with coronary heart disease or at least one of its risk factors. Methods Twenty-six health centres around Finland were randomly selected for the purpose of identifying, over a two-week period in April 2005, patients meeting the inclusion criteria of coronary heart disease or one of its risk factors. GPs and identified patients (n = 1880) were asked to complete surveys that included a question about the patient's MetS status. A trained nurse conducted health checks (n = 1180) of the identified patients, utilising criteria of MetS modified from the National Cholesterol Program. Data from the GPs' survey were compared with those from the health check to establish the extent of congruence of identification of MetS. Results Almost half (49.4%) of the patients met the criteria of MetS as established by objective measures. However, in the GPs' survey responses, only 28.5% of the patients were identified as having MetS. Additionally, these groups of MetS patients were not congruent. The sensitivity of the GPs' diagnosis of MetS was 0.31 with a specificity of 0.73. Only 7.1% of the study patients stated that they were suffering from MetS. Conclusion Detection of MetS is inaccurate among GPs in Finland. Most patients were not aware of having MetS. The practical relevance of MetS in primary care should be reconsidered.